"Quit Masturbation, Change Failure": The Process, Essence, and Reflection of the Identity Construction in the Abstinence Internet Organization. Issue 3 (31st March 2021) - Apei, Song
Abstract: In response to the problem of the social integration of masturbation groups, existing studies have simplified it into a one-way, passive correction process, which has mixed heterogeneous organizational groups and ignored the interactive meanings displayed by several in this process. Through the participatory observation and in-depth interviews with the masturbation abstainers in the network group organization, this article presents the abstinence process of the masturbation group in the internet platform. The qualitative study found that the use of symbols by Internet organizations with the experience of "evil sex" and "moral irrationality" has strengthened the stigma of the masturbation group, but at the same time provided a religious compensatory role for quit masturbation. Religious compensation within a certain period of time formed a moral order and strengthened self-identification. In essence, the order established by the network organization is supported by the "sex addiction-Buddhism" interpretation system proposed by the administrator. With the change of power within the network organization, the original firm interpretation system quickly formed a new discourse. This change of management has not triggered conflicts between masturbation guards and the maintenance of the old system but has been accepted because the moral constraints and health regulations in the new interpretation system are still orderly. This acceptance process clearly demonstrates the constant desire of the masturbator for security and certainty and the desire for the order to accommodate his own qualities.